Forma zastrzeżenia dotyczącego opóźnienia dostawy na gruncie art. 30 ust. 3 konwencji CMR. Glosa do wyroku Sądu Najwyższego z 26 stycznia 2024 r., II CSKP 1971/22 - Dąbrowski, Daniel (PRAWO i WIĘŹ, 2026)
The commentary concerns the judgment of the Supreme Court of 26 January 2024, in which the Court interpreted Article 30(3) of the CMR Convention. This provision stipulates that a reservation concerning delay in delivery must be made “in writing” within 21 days. The Court held that the form “in writing” means that a statement with an original signature must be submitted, which excludes, inter alia, e-mail as an effective form of reservation. The author of the commentary criticises this position, arguing that the Court’s interpretation is too restrictive and does not take into account the function to be fulfilled by the provision in question. In the author’s opinion, a correct interpretation in accordance with the rules of the Vienna Convention on the Law of Treaties and taking into account the dynamic development of communication methods in recent years leads to the conclusion that electronic communication can, in principle, be treated as equivalent to the “in writing” form.